Constraining source properties of the 1509, 1766 and 1894 Istanbul earthquakes - Yenihayat, Nesrin. (Thesis (Ph.D.)-Bogazici University.Kandilli Observatory and Earthquake Research Institute, 2022., 2022)
In this thesis, stochastic simulations were performed for the 10 September 1509, 22 May 1766, and 10 July 1894 Istanbul earthquakes to constrain their source parame ters with a detailed characterisation and classification of associated damages and their distributions. Damage information was obtained as spatial distributions of observed data assembled from various sources and interpreted on the MMI scale. Using a finite fault simulation approach, numerous scenarios were modeled with calibrated and validated source, path and site parameters. In calibration, simulations were performed for 59 recordings of the 26 September 2019 Silivri (Mw=5.8) earth quake. In order to test our model on a larger Marmara earthquake recordings obtained at 19 stations of the 17 August 1999 Kocaeli (Mw=7.4) earthquake were also simulated. Through an iterative selection of source parameters and comparison of simulation based synthetic intensity distributions with intensities assessed from actual damage, evaluations of source parameters of three earthquakes were made. Findings indicated that most likely the magnitude of the 1894 Istanbul earthquake was Mw=[6.8 to 6.9], and its epicenter was either at the midpoint of the Prince Islands segment with a 42 km rupture or at the intersection of the Prince Islands segment with the Izmit segment as a 60 km total rupture. The 1766 earthquake likely had a rupture length of about 80 km along the Central Marmara Fault with a magnitude of Mw=[7.0 to 7.1]. Our findings suggested that the 1509 earthquake most probably occurred as a combined rupture of the Prince Islands segment and the Central Marmara Fault, and created a 120 km rupture with a magnitude of Mw=7.6.
Keywords: Earthquakes -- Istanbul (Turkey)